2019
DOI: 10.1053/j.gastro.2019.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Fibrogenic Activity of MECP2 Is Regulated by Phosphorylation in Hepatic Stellate Cells

Abstract: Background & AimsMethyl-CpG binding protein 2, MECP2, which binds to methylated regions of DNA to regulate transcription, is expressed by hepatic stellate cells (HSCs) and is required for development of liver fibrosis in mice. We investigated the effects of MECP2 deletion from HSCs on their transcriptome and of phosphorylation of MECP2 on HSC phenotype and liver fibrosis.MethodsWe isolated HSCs from Mecp2–/y mice and wild-type (control) mice. HSCs were activated in culture and used in array analyses of messeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 52 publications
0
22
0
1
Order By: Relevance
“…Currently, it is known that epigenetic modifications of liver fibrosis‐related genes in liver fibrosis development . Epigenetic provides to a heritable modulation in gene expression that does not alter the DNA itself .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is known that epigenetic modifications of liver fibrosis‐related genes in liver fibrosis development . Epigenetic provides to a heritable modulation in gene expression that does not alter the DNA itself .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it is known that epigenetic modifications of liver fibrosis-related genes in liver fibrosis development. [4][5][6] Epigenetic provides to a heritable modulation in gene expression that does not alter the DNA itself. 7,8 Epigenetic influences generally refer to aberrant DNA methylation and non-coding RNA (ncRNA) modifications.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, MeCP2 induces the expression of ASH1, a histone methyltransferase that induces transcriptional activation of profibrogenic genes via H3K4 methylation [ 56 ]. Furthermore, a very recent study demonstrated that HIPK2-mediated Ser80 phosphorylation of MeCP2 is required for HSC transdifferentiation [ 57 ]. Mutation of Ser80 to alanine reduces the affinity of MeCP2 to multiple gene promoter sequences, therefore this post-translational modification is also important for DNA binding [ 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Phosphorylated MeCP2-421 and MeCP2-80 are the two major event in keeping homeostasis of cell function under normal condition that is called Yin and Yang. 34,35 It is shown that inhibition of phosphorylated MeCP2-80 increased neuronal activity, and MeCP2-80 phosphorylation reduced hepatic stellate cells proliferation and liver fibrosis 36 ; in contrast to MeCP2-80 phosphorylation, the neuronal activity and gene activation are associated with phosphorylation of MeCP2-421. 34,37 In our study, the increased P-MeCP2 421 instead of P-MeCP2-80 was seen in the human PVR membranes; more likely, the balance between P-MeCP2-80 and P-MeCP421 was lost in the process of development of PVR.…”
Section: Discussionmentioning
confidence: 99%